Mapping the Literature on the Effectiveness of Conflict Management in Inclusive Education - Slamet Riyadi; I Wayan Karang Utama; Arisman Sabir; Ahmad Muktamar (Westscience Press, 2024)
This study provides a comprehensive bibliometric analysis of the literature on inclusive education, revealing key thematic clusters, research trends, potential research opportunities, and author collaboration networks. The central theme of inclusive education is examined through the lens of various interconnected topics, including teaching strategies, attitudes and self-efficacy, stakeholder perceptions, and policy implementation. The analysis of research trends highlights a dynamic evolution in the field, with growing attention to innovative teaching methods, effective teacher training, and inclusive educational practices. The study identifies several potential research areas, such as the development of differentiated instruction techniques, the impact of culturally responsive teaching, and the role of community involvement in supporting inclusive education. The author collaboration network reveals distinct research clusters and influential researchers, emphasizing the importance of collaborative efforts in advancing the field. Overall, this bibliometric analysis provides valuable insights into the current state of research in inclusive education and outlines crucial areas for future investigation to enhance educational outcomes for all students.